Positive Adjustment Among American Repatriated Prisoners of the Vietnam War: Modeling the Long-Term Effects of Captivity. (November 2015) - King, Daniel W.; King, Lynda A.; Park, Crystal L.; Lee, Lewina O.; Pless Kaiser, Anica; Spiro, Avron; Moore, Jeffrey L.; Kaloupek, Danny G.; Keane, Terence M.
A longitudinal life span model of factors contributing to later-life positive adjustment was tested on 567 American repatriated prisoners from the Vietnam War. This model encompassed demographics at time of capture and attributes assessed after return to the United States (reports of torture and mental distress) and approximately three decades later (later-life stressors, perceived social support, positive appraisal of military experiences, and positive adjustment). Age and education at time of capture and physical torture were associated with repatriation mental distress, which directly predicted poorer adjustment 30 years later. Physical torture also had a salutary effect, enhancing later-life positive appraisal of military experiences. Later-life events were directly and indirectly (through concerns about retirement) associated with positive adjustment. Results suggest that the personal resources of older age and more education and early-life adverse experiences can have cascading effects over the life span to impact well-being in both positive and negative ways.